Degree of Glutathione Deficiency and Redox Imbalance Depend on Subtype of Mitochondrial Disease and Clinical Status - Enns, Gregory M.; Moore, Tereza; Le, Anthony; Atkuri, Kondala; Shah, Monisha K.; Cusmano-Ozog, Kristina; Niemi, Anna-Kaisa; Cowan, Tina M. (PLOS ONE, 2014)
Mitochondrial disorders are associated with decreased energy production and redox imbalance. Glutathione plays a central role in redox signaling and protecting cells from oxidative damage. In order to understand the consequences of mitochondrial dysfunction on in vivo redox status, and to determine how this varies by mitochondrial disease subtype and clinical severity, we used a sensitive tandem mass spectrometry assay to precisely quantify whole blood reduced (GSH) and oxidized (GSSG) glutathione levels in a large cohort of mitochondrial disorder patients. Glutathione redox potential was calculated using the Nernst equation. Compared to healthy controls (n = 59), mitochondrial disease patients (n = 58) as a group showed significant redox imbalance (redox potential −251 mV±9.7, p<0.0001) with an increased level of oxidation by ∼9 mV compared to controls (−260 mV±6.4). Underlying this abnormality were significantly lower whole blood GSH levels (p = 0.0008) and GSH/GSSG ratio (p = 0.0002), and significantly higher GSSG levels (p<0.0001) in mitochondrial disease patients compared to controls. Redox potential was significantly more oxidized in all mitochondrial disease subgroups including Leigh syndrome (n = 15), electron transport chain abnormalities (n = 10), mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (n = 8), mtDNA deletion syndrome (n = 7), mtDNA depletion syndrome (n = 7), and miscellaneous other mitochondrial disorders (n = 11). Patients hospitalized in metabolic crisis (n = 7) showed the greatest degree of redox imbalance at −242 mV±7. Peripheral whole blood GSH and GSSG levels are promising biomarkers of mitochondrial dysfunction, and may give insights into the contribution of oxidative stress to the pathophysiology of the various mitochondrial disorders. In particular, evaluation of redox potential may be useful in monitoring of clinical status or response to redox-modulating therapies in clinical trials.